Hybrid Chaotic Hash Function based on HAIFA Structure - Haralambie, Florin; Rincu, Cristian-Iulian; Bartusica, Razvan; Nichita, Mihai-Virgil (IEEE International Conference on Communications (2003), 2024)
The everchanging security environment demands new, robust and customizable hash functions that integrate novel techniques to improve performance. This paper evaluates the performance of a hybrid chaotic hash function that uses the HAIFA structure aiming to improve security and customizability. It serves as a hash or HMAC function with uses in dedicated, special purpose applications focusing on maintaining or improving security. The performances of the hybrid chaotic hash function that uses the HAIFA Structure are compared to the widely used SHA-256 hashing algorithm and to a chaotic hash algorithm with induced DNA sequences. The security analysis is done by measuring and comparing the message digest character distribution, linear complexity, sensitivity, confusion and diffusion.